Comparison of marpe and alt-ramec protocol in correcting skeletal transverse discrepancy in young adults: a randomized controlled clinical trial - Allam, Amira Hussein Ahmed Mohamed (2024)
The skeletal deficiency could be expressed in the maxilla sagittally, vertically, and transversally. The most effective treatment for transverse maxillary deficiency in growing children and adolescents is still rapid maxillary expansion (RME). In adults, mini-screw-assisted rapid palatal expansion (MARPE) proved to be the efficient method for overcoming all dentoalveolar drawbacks. In treating adult patients with anteroposterior deficient maxilla (skeletal class III), the clinician had to decide between an invasive surgical approach to resolve the skeletal imbalance or a camouflage therapy to mask the class III malocclusion. However, in younger patients, alternate rapid maxillary expansion and constriction (ALT-RAMEC) is the treatment of choice. In this study, the 7-week ALT-RAMEC protocol was modified and combined with MARPE to evaluate its efficiency and advantages over conventional MARPE in young adult ages. Twenty-nine patients with transverse maxillary deficiency (mean age of 21.3) were randomly assigned to two groups. The conventional group received MARPE with its conventional rate of expansion, while the ALT-RAMEC group was treated with a combination of MARPE with ALT-RAMEC modified protocol. The efficiency of expansion, circummaxillary sutural displacement, dentoskeletal, respiratory, and clinical periodontal effects were all assessed. Analysis of the change before and after intervention was examined using paired t-tests while analysis of the parameters comparing the two groups was examined using an independent t-test. For variables that were not normally distributed, the p-value was obtained from Bootstrap for pairwise comparison (BCA). The analysis of covariance (ANCOVA) was used when the baseline data was significantly different between groups. The results showed 100% efficiency of both techniques to produce expansion in both groups. Mid-palatal, frontonasal, and intermaxillary sutures displaced and increased significantly (p ≤ 0.001) in width after treatment with both protocols, while the zygomaticomaxillary sutures compressed and showed a significant decrease in width with conventional MARPE, though, expanded and increased significantly in width with the ALT-RAMEC group (p < 0.001). The dentoskeletal effects revealed that conventional MARPE produced a buccal molar tipping while ALT-RAMEC showed a more bodily movement of the anchor molars. There were no additional effects of ALT-RAMEC on airway volume than MARPE did. Both protocols significantly increased the nasal cavity and oropharynx volumes and significantly decreased the nasopharynx and maxillary sinus volumes (p < 0.001) with a non-significant difference between groups (p > 0.05). The periodontium conditions were not correlated to the activation protocols in the current study, but the longer treatment time in the ALT-RAMEC group proved to have a more negative impact on the surrounding gingiva than conventional MARPE did. The modified ALT-RAMEC technique is a promising protocol sufficient to expand the maxilla transversely without tipping the anchored teeth in young adult patients.